PENGEMBANGAN APLIKASI PENGELOLAAN DATA ASET DENGAN MENERAPKAN QR CODE GENERATOR DI LABORATORIUM KOMPUTER FAKULTAS TEKNOLOGI INFORMASI - COMPUTING INFORMATIKA; yudi herdiana; Khilda Nistrina; Andika Dwi Putra (COMPUTING | Jurnal Informatika, 2022)
The management of computer laboratory asset data at the Faculty of Information Technology, Bale University Bandung (FTI UNIBBA) still uses common applications such as Microsoft Excel, Microsoft Word, and so on. So that the development of an application is carried out to manage asset data, where the application also applies a QR Code generator to make it easier to identify assets. The method used in collecting data uses the method of interviews, observations, and literature studies. As for the application development method using the System Development Life Circle (SDLC) waterfall model method which has several stages including system analysis, system design, coding, and program trials. This application was created using the codeigniter 3 and Bootstrap 3 frameworks as its application framework and uses MySQL as its database. The programming language that is focused uses the PHP programming language, so the application is web-based. For the design of the application, it uses Unified Modelling Language (UML) as a modeling language which is an object-oriented modeling method. The algorithm that is focused on the application is an engineering algorithm or process to generate a QR Code based on existing asset data. With this computer laboratory asset data management application, it will make it easier to classify assets and make it easier to manage computer laboratory asset data.